Analysis of supply chain management in overcoming the bullwhip effect of mineral water - Fitriyanti; Eman Sulaiman; Vina Andita Pratiwi; Cici Ningsih (Institute of Computer Science (IOCS), 2022)
This study aims to identify the cause of the bullwhip effect and find solutions to overcome it. The research object is the demand and sale of mineral water for January – May 2021 at Alfamart SPBU BIMA Cirebon. The phenomenon of changes in customer demand which is relatively stable every day for weekly or bi-weekly orders from the Cirebon Distribution Center (DC), will receive orders that are more stable than the demand faced by retail companies. Sole distributor demand will also be stable, impacting the costs incurred by companies in storage. One way to analyze some of the causes of the bullwhip effect in a company is to analyze the factors causing it so that the supply chain of mineral water products runs smoothly. The bullwhip value needs to be measured to determine the bullwhip effect can be done using the data aggregation method by Fransoo and Wouters.